Length, age and estimated back-calculated length of pike (Esox lucius) in relation to water temperature from Lake Mälaren and the Swedish Baltic Sea archipelago 1963-2019 - Time series of monthly average surface water temperature (<0.5m) during summer at Kvädöfjärden (Baltic Sea) and Lake Mälaren. - Östman, Örjan; Berggren, Terese; Sundblad, Göran (Swedish University of Agricultural Sciences, 2022)
Data on estimated back-calculated body growth from both harvested and non-harvested populations of northern pike over 50 years along the Baltic Sea coast and in Lake Mälaren, Sweden. The aim is to study spatial and temporal variation in body growth, and especially how body growth relates to variation in water temperature. Data on surface water temperature from Kvädöfjärden (Batltic Sea) and Lake Mälaren during the study period. See detailed description of methods and analyses in the original article.

Time series of monthly average surface water temperature during summer at Kvädöfjärden (Baltic Sea) and Lake Mälaren.

Data på uppskattad tillbakatillväxt av gäddor från över 50 år från både fiskade och ofiskade områden längs svensk Östersjökust och Mälaren. Syftet är att studera hur tillväxtmönster har varierat över tid och rum, speciellt hur kroppstillväxt relaterar till variation i vattentemperatur. Data på ytvattentemperaturer från Kvädöfjärden (Östersjön) och Mälaren. Se utförlig metodbeskrivning i originalartikeln.
Tidsserie av medeltemperatur av ytvatten (<0.5 m) per månad under sommaren i Kvädöfjärden (Östersjön) och Mälaren.
Längd, ålder och uppskattade tillbakaräknade längder av gäddor (Esox lucis) i förhållande till vattentemperatur från Mälaren och svenska Östersjökusten 1963-2019 - Vattentemperaturer i Mälaren och Kvädöfjärden.
Keywords: WATER TEMPERATURE; climate change impact; klimatförändringarnas konsekvenser; Ecology; Ekologi; Evolutionary Biology; Evolutionsbiologi; Biota; Biologi och ekologi